THE ROLE OF THE SCHOOL COMMITTEE IN IMPROVING THE QUALITY OF STUDENT RELIGIOSITY AT SMP NEGERI ARUN - Almuhajir, Almuhajir (STIT Al-Ittihadiyah Labuhanbatu Utara, 2023)
This study aims to explain the role of the school committee in improving the quality of student religiosity at SMP Negeri Arun. This research is a qualitative research using a descriptive approach. Data sources consist of primary data and secondary data. To obtain accurate data, researchers conducted three data collection techniques, namely observation, interviews, and documentation, while data analysis techniques consisted of data collection, data condensation, data presentation and drawing conclusions. The results showed that the role of the school committee in improving the quality of student religiosity at SMP Negeri Arun is as an advisory agency in determining and implementing educational policies in the field of student religiosity, as a supporting agency namely raising funds to support the implementation of student religiosity development activities, as a controlling agency for student religiosity self-development activities, and as a mediator agency for schools with student guardians and government related to student religiosity issues.